From Crime to Terrorism: life-Circumstances and Criminal Careers of Terrorist Suspects - Rodermond, Elanie (Crime & delinquency, 2023)
It is widely acknowledged that factors such as previous offending and unemployment increase the risk of offending, but it remains unclear to what extent this also holds true for terrorist suspects. Using register-data on individuals suspected of a terrorist offense in the Netherlands, the present study takes on a life-course criminological approach to study the background and criminal career of terrorist suspects. Moreover, we compare their background to that of general criminal suspects and members of the general population. Our findings support the idea of a ?new? crime-terror nexus at the individual level and show similarities between terrorist suspects and regular suspects.